AI Ethics A Textbook - Boddington, Paula (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book introduces readers to critical ethical concerns in the development and use of artificial intelligence. Offering clear and accessible information on central concepts and debates in AI ethics, it explores how related problems are now forcing us to address fundamental, age-old questions about human life, value, and meaning. In addition, the book shows how foundational and theoretical issues relate to concrete controversies, with an emphasis on understanding how ethical questions play out in practice. All topics are explored in depth, with clear explanations of relevant debates in ethics and philosophy, drawing on both historical and current sources. Questions in AI ethics are explored in the context of related issues in technology, regulation, society, religion, and culture, to help readers gain a nuanced understanding of the scope of AI ethics within broader debates and concerns. Written with both students and educators in mind, the book is easy to use, with key terms clearly explained, and numerous exercises designed to stretch and challenge. It offers readers essential insights into the evolving field of AI ethics. Moreover, it presents a range of methods and strategies that can be used to analyse and understand ethical questions, which are illustrated throughout with case studies.
Chapter 1. Introduction: Why AI Ethics? -- Chapter 2. The Rise of AI Ethics -- Chapter 3. AI, Philosophy of Technology, and Ethics -- Chapter 4. Methods in Applied Ethics -- Chapter 5. Humans and Intelligent Machines: Underlying Values -- Chapter 6. Normative Ethical Theory and the Challenges from AI Ethics -- Chapter 7. Philosophy for AI Ethics: Metaethics, Metaphysics, and More -- Chapter 8. Persons and AI -- Chapter 9. Individuals, Society, and AI: Online Communication -- Chapter 10. Towards the Future with AI: Work and Superintelligence -- Chapter 11. Our Future with AI: Future Projections and Moral Machines.
Keywords: Artificial intelligence; Ethics; Technology -- Moral and ethical aspects; Normativity (Ethics).; Artificial Intelligence; Moral Philosophy and Applied Ethics; Ethics of Technology; Normative Ethics